ANALISIS PENGARUH ECONOMICS VALUE ADDED (EVA), RETURN ON INVESMENT (ROI) DAN PRICE EARNING RATIO (PER) TERHADAP RETURN SAHAM PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2014 - Laela Kartini, 12.05.51.0180; Irsad, Moch. (Students' Journal of Economic and Management, 2016)
High demand of board make the property sector is growing fast in Indonesia. Regarding of that, many investors have been investing their shares in real estate and property sector. Furthermore, investors also need funds from external sources. External sources funds can be obtained through the capital market. The purpose of this research is to analyze the influence of Economics Value Added (EVA), Return On Investment (ROI) and Price Earning Ratio (PER) to Stock Returns of Real Estate and Property company that listed in Indonesia Stock Exchange in the period of 2012 - 2014. This study using data from the Indonesian Capital Market Directory (ICMD) and the Indonesia Stock Exchange (IDX). The population in this study is 57 companies, by using purposive sampling method the sample that used is 48 companies. The analysis technique used is multiple regression analysis in order to describe overall of the relation between variables. The results showed that the Economics Value Added (EVA) and Price Earning Ratio (PER) have a negative effect to the Stock Return. Meanwhile, Return On Investment (ROI) Return has a positive effect to the Stocks Return.Keywords: Economics Value Added (EVA), Return On Investment (ROI), Price Earning Ratio (PER), Stock Return.               .